Analysis of the Coaching Leadership Model for Elementary School Principals - Masoudi, Maral; Hamidifar, Fatemeh; Khorshidi, Abbas; Delgoshaei, Yalda (Iranian Journal of Educational Sociology, 2022)
Purpose: The objective of this study is to develop and validate a comprehensive coaching leadership model for elementary school principals.Methodology: This research employed a mixed-methods approach, combining qualitative and quantitative techniques. The qualitative component involved semi-structured interviews with 15 experts in educational leadership to identify key components of the coaching model. The quantitative component included a survey distributed to 353 elementary school principals, with data analyzed using confirmatory factor analysis and structural equation modeling (SEM) through SPSSwin20 and SMART PLS 8 software. The reliability and validity of the questionnaire were confirmed with a Cronbach's alpha of 0.85.Findings: The findings indicate that the proposed coaching leadership model significantly improves principals' competencies in instructional leadership, organizational management, and relationship-building. Confirmatory factor analysis demonstrated strong factor loadings and satisfactory model fit indices (GFI = 0.934, CFI = 0.944, RMSEA = 0.064). The model's effectiveness was further supported by enhanced teacher performance and a positive school climate, corroborating existing research on the benefits of coaching in educational leadership. The study identified key strategies such as professional growth, networking, and organizational support as crucial for effective coaching.Conclusion: The coaching leadership model developed in this study holds significant promise for enhancing the leadership competencies of elementary school principals. By providing personalized support and fostering a culture of continuous improvement, coaching can empower principals to effectively manage school operations, support teacher development, and improve student learning outcomes. This model offers a practical framework for implementing coaching programs tailored to the specific needs of school principals, with implications for broader educational policy and practice.